Unveiling inequalities: Racial, ethnic, and socioeconomic disparities in diabetes: Findings from the 2007-2020 NHANES data among U.S. adults - Yangyang Deng; Mohammad Moniruzzaman; Breanna Rogers; Lu Hu; Ram Jagannathan; Kosuke Tamura (Preventive Medicine Reports)
Objective: Despite persistent disparities in diabetes prevalence among racial and ethnic minorities, there remains a significant lack of understanding regarding the intersectionality of racial and ethnic groups and socioeconomic status (SES) with diabetes. Methods: The data came from the National Health and Nutrition Examination Survey (NHANES; N = 30,754, mean age = 47.4) using cross-sectional survey cycles from 2007 to 2008 through 2017–2020. Diabetes status was self-reported by physician diagnosis. Sociodemographic factors included racial and ethnic groups and SES. Weighted Poisson models were used to examine the association of racial and ethnic groups and SES with diabetes, stratified by age groups (20–44, 45–64, 65–79), sex, and racial and ethnic groups for SES, separately. Results: Non-Hispanic Black, Hispanic, and other adults had a 47 %, 31 %, and 76 % higher prevalence of diabetes than non-Hispanic White adults, while adults from low and middle SES compared to high SES had a 37 % and 22 % higher prevalence of diabetes. Non-Hispanic Black, Hispanic, and other adults aged 45–64 years had a 45 %, 34 %, and 78 % higher prevalence of diabetes, and low and middle SES had a 57 % and 32 % higher prevalence of diabetes. Similar patterns were observed for adults aged 65–79. Males among non-Hispanic Black, Hispanic, and other adults and females from low and middle-SES families had a higher prevalence of diabetes. Conclusion: Minority groups, middle and older-aged adults, males from minority groups, and females from low SES had a greater prevalence of diabetes. Effective interventions should prioritize tailoring efforts to specific minoritized and low SES groups to address diabetes disparities.